Chromatin Texture from Hematoxylin Stained Thyroid Lesions - Olga Ferrer-Roca; José A. Pérez Gómez; Maritza Estévez (Analytical Cellular Pathology)
Quantitative aspects of cytology and histology should be considered in diagnostic standardisation processes. The present paper summarises the cytological differences detected in 75 thyroid lesions using a computerized textural analysis.